Abnormal presentation of ascending cholangitis - Scaife, Mark (Clin Case Rep, 2018)
Ventriculo‐peritoneal, ‐gallbladder, ‐pleural, ‐atrial, and ‐jugular shunts are all viable options in the treatment of hydrocephalus 1, 2, 3. Retrieval of these catheters can often be very difficult and may be unsuccessful or incomplete. Retained catheters can result in unforeseen and unexpected complications.